"At times I kinda felt I was in an institution": Supportive housing for transition age youth and young adults. (February 2017) - Munson, Michelle R.; Stanhope, Victoria; Small, Latoya; Atterbury, Kendall
Abstract: Housing stability is essential for young adult development. Older youth and young adults transitioning from public systems of care, such as foster care, the public mental health system and residential settings, commonly experience high levels of transience and housing instability. In recent years, supportive housing policies and programs have emerged to address this situation, yet we know little about whether (or not) new programs are meeting the needs of youth in transition, and, if so, how they are addressing the unique developmental, social, and emotional needs of this population. This study is one of the first to speak directly with young adults living in a supportive housing program designed specifically for youth transitioning out of children's systems of care. Study participants spoke about both their overall transition experience and their views on the housing program where they reside. The study conducted four focus groups ( N = 26) with transitioning youth and young adults, ages 18 to 25 (Mean age = 22), in order to explore the following three broad research questions: 1) what is it like to make the transition to adulthood from public children's systems of care?; 2) how does the supportive housing model they reside in shape their transition experiences?; and, 3) how do they experience the services and staff who are part of the program? Data analysis included grounded theory coding techniques and constant comparison with four coders. Results suggest that participants feel like they continue to be treated as children, and they receive mixed messages regarding their need to be increasingly autonomous, yet follow the rules. Finally, they reported specific aspects of what they found to be helpful in both staff relationships and overall program components. These themes constitute the results of the study. Findings underscore the importance of both listening directly to service users, and developing young adult supportive housing programming expressly designed to meet the unique needs of marginalized young adults transitioning to increased independence and self-sufficiency. Highlights: The first focus group study examining data from transition age youth themselves on their views on a supportive housing model Staff working in transitional supported housing programs require specific training to support youth in finding permanent housing Results contextualize the developmental challenges of moving toward independence from institutional childhood Results can provide information to supportive housing models currently being piloted throughout the country